Implementation Model Prototyping In Application Design of Halal Food Product Detection For Overseas Muslim Students - Fandisya Rahman; Bambang Minto Basuki (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2023)
In the age of globalization, the production and trading of food have become more widespread, and consumers, particularly those who follow the Islamic faith, require access to information about the halal status of the products they consume. It is crucial to provide accurate and relevant information to them regarding the halal nature of the products they buy. To cater to this need, many people are using barcode scanners via mobile platforms to obtain product information. These barcode scanners use optical scanners called code readers, and they are popular as they provide a quick and efficient way of obtaining information. Creating a barcode application using the prototyping method is an effective solution that involves several steps, such as gathering and analyzing requirements, rapid design, building a prototype, user evaluation, and refining the prototype. The programming language Kotlin is used to create these applications, which support building Android applications on the Java Virtual Machine Platform (JVM). The use of Kotlin, which is statically expressed and executed, makes the process of developing these applications efficient and straightforward. In summary, developing a barcode application using the prototyping method and Kotlin is an excellent solution to provide consumers with accurate and accessible information about the halal status of food products they consume.